Arithmetic Sequences and Series

  1. Arithmetic Sequence

    Examples

    Find the general term for the following sequences both recursively and explicitly:

    1. 2,6,10,14,18,22, ...

    2.  -5,-3,-1,1,3,...

    3. 1,4,7,10,13,16,...

    4. -1,10,21,32,43,54,...

    5. 3,0,-3,-6,-9,-12,...

    Solution

    All of these have one thing in common.  To get to the next term we add a fixed number. 
     

    1. Add four to obtain the next term. Thus

              an+1 = an + 4,     a1 = 2   

      To find an explicit expression, we use the following reasoning.  To get the first term, we start with 2 and add no 4's.  To get to the second term we start with 2 and add one 4.  To get to the third term, we start with 2 and add two 4's.  To get the the fourth term we start with 2 and add three 4's.  To get to the nth term, we start with 2 and add n - 1 four.  Hence

              an = 2 + 4(n - 1)

    2.  Add two to obtain the next term. Thus

              an+1 = an + 2,     a1 = -5   

      To find an explicit expression, we use the same reasoning as in part "A".  To get the first term, we start with -5 and add no 2's.  To get to the second term we start with -5 and add one 2.  To get to the third term, we start with -5 and add two 2's.  To get the the fourth term we start with -5 and add three 2's.  To get to the nth term, we start with -5 and add n - 1 twos.  Hence

              an = -5 + 2(n - 1)

    3. As in the preceding exercises,

              an+1 = an + 3,     a1 = 1

      and

              an = 1 + 3(n - 1)

    4. We have

              an+1 = an + 11,     a1 = -1

      and

              an = -1 + 11(n - 1)

    5. Finally,

              an+1 = an - 3,     a1 = 3

      and

              an = 3 -  3(n - 1)

                

                 Definition  
    A sequence with general term

              an+1 = an + d

    is called an arithmetic sequence.


    This definition defines an arithmetic sequence recursively.  The next theorem shows how to find an explicit form for an arithmetic sequence.


                 Theorem
    An arithmetic sequence with 

              an+1 = an + d  

    has explicit form

                an = a1 + (n - 1)d

     

    Proof:  (by induction)

    For n = 1, we have 

            a1 = a1 + (1 - 1)d  (true)

    Assume that the theorem is true for n = k - 1, hence

            ak-1 = a1 + (k - 1 - 1)d = a1 + (k - 2)d

    Then 

            ak = ak-1 + d = a1 + (k - 2)d + d

            = a1 + kd - 2d + d = a1 + kd - d = a1 + (k - 1)d

    Hence by mathematical induction, the theorem is true.

    Example:  

    Suppose that a1 = 4 and d = 2 then the sequence is 

            4,6,8,...,(4 + (n - 1)d),...

     

    Example

    Suppose that the 13th term of an arithmetic sequence is 46 and the fourth term is 100.  Find the expression for the general term.

    Solution

    We have 

            46 = a1 + d(13 - 1) = a1 + 12d

    and

            100 = a1 + d(4 - 1) = a1 + 3d

    Subtracting the two equations gives

            -54 = 9d

    or        

            d = -6

    Putting this back into the first equation gives

            46 = a1 + 12(-6)

    or   

            a1 = 118

    We can conclude that 

            an = 118 - 6(n - 1)


  2. The Arithmetic Series

    The following theorem provides us with an easy way to calculate the arithmetic series.


              Theorem
    If

              an =  a1 + (n - 1)d

    is an arithmetic sequence then the sum of the sequence is

             SnS i=1 an =  n/2 (a1 + an)

     

    Proof:

            Sn = S i=1 an = a1 + a2 + ... + an-1 + an

            = a1 + (a1 + d)  + ... +(a1 + (n - 2)d) + (a1 + (n - 1)d)

            The sum can also be written by working backwards from the last term, that is to get to the previous term, subtract d.

            Sn = S i=1 an = an + an-1 + ... + a2 + a1

            = (a1 + (n - 1)d) + (a1 + (n - 2)d) + ... + (a1 + d)+ a1  

    Since these are the same we can add them together to get 2S.

            Sn = a1                    +    (a1 + d)        + ... + (a1 + (n - 2)d) + (a1 + (n - 1)d)
            Sn = (a1 + (n - 1)d) + (a1 + (n - 2)d) + ... + (a1 + d)           +  a1


            2Sn = [a1 + (a1 + (n - 1)d)] + [a1 + (a1 + (n - 1)d)] + ... 
                    +[a1 + (a1 + (n - 1)d)] + [a1 + (a1 + (n - 1)d)] 

            =  [a1 + an] + [a1 + an] +... + [a1 + an] + [a1 + an

            = n[a1 + an]

            Hence 

            Sn =  n/2 [a1 + an]

     

    Example:  

    Find 

            3 + 7 + 11 + 15  + ... + 35

    Solution:

    We have 

            a1 = 3, an = 35, d = 4

    To find n we note that 

            35 = 3 +  (n - 1)4

    so that 

            32 = (n - 1)4

    Dividing gives

            8 = n - 1

    Hence

            n = 9

    Now we are ready to use the formula

            Sn = 9/2 (3 + 35) = 171

     

    Exercise:  

    Suppose that the sum of the first 18 terms of an arithmetic sequence is -45 and 

            d = -9 

    find the first term.

     

    Application  

    Suppose that you play black jack at Harrah's on June 1 and lose $1,000.  Tomorrow you bet and lose $15 less.  Each day you lose $15 less that your previous loss.  What will your total losses be for the 30 days of June?

    Solution

    This is an arithmetic series with

            a1 = 1000 

    and

            d = -15

    We can calculate

            a30 = 1000 - 15(30 - 1) = 565

    Now we use the formula

            S30 = 30/2 (1000 + 565) = 23,475

    You will lose a total of $23,475 during June.

 



Back to the College Algebra Part II (Math 103B) Site

Back to the LTCC Math Department Page

e-mail Questions and Suggestions